2016
DOI: 10.1093/bmb/ldw035
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET/CT imaging of cardiac and vascular inflammation and infection

Abstract: Larger prospective studies are needed to validate the superiority of F-18 FDG PET/CT imaging over conventional anatomic imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 110 publications
1
38
0
3
Order By: Relevance
“…A single study utilising 67 Ga scintigraphy has reported an increased uptake in the RV free wall in patients with ARVC compared to controls [18]. FDG-PET is an established method for assessing myocardial inflammation and is used increasingly in the clinical work-up of patients with clinically suspected myocarditis [19].…”
Section: Discussionmentioning
confidence: 99%
“…A single study utilising 67 Ga scintigraphy has reported an increased uptake in the RV free wall in patients with ARVC compared to controls [18]. FDG-PET is an established method for assessing myocardial inflammation and is used increasingly in the clinical work-up of patients with clinically suspected myocarditis [19].…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG remains the most commonly used PET tracer in clinical application. Its lack of specificity in differentiating sterile inflammation from infection, however, represents a significant limitation, especially in the postoperative period (8). An unmet need therefore remains in the clinical differentiation of inflammation from infection.…”
Section: Replymentioning
confidence: 99%
“…It is also important to differentiate superficial wound infection from an actual device infection, as the two types of infection are managed differently. Whereas deep infection affecting the device requires removal of the device, with its attendant risk of mortality and morbidity, superficial wound infection requires only local wound care and parenteral antibiotics (11). Clinical assessment is often not sufficient to make this distinction (12).…”
Section: Imaging Cellular Metabolism: 18 F-fdgmentioning
confidence: 99%